Caecal bacterial composition of broiler chickens affected by porang glucomannan - Larasati, Y. N.; Harmayani, E.; Widada, J.; Nurliyani, N.; Perdinan, A. (Diponegoro University, 2021)
Glucomannan is consisted of D-glucose and D-mannose with β-1.4 linkages. Poultry had no enzyme to digest β linkage so that porang (Amorphophallus onchophyllus) glucomannan could be a prebiotic candidate. The study purposed to determine the effect of porang glucomannan on caecum bacterial composition (similarity, diversity, grouping of bacteria) using Terminal Restriction Fragment Length Polymorphisms method and performance (body weight gain, feed intake, feed conversion ratio) of broiler chickens. One hundred and eighty unsexed day old chicks (DOC) were divided into 6 treat-ments and 3 replicates (10 birds each) using completely randomized design (CRD). The treatments were P0 (basal feed), P1 (basal feed + 0.05% porang glucomannan), P2 (basal feed + 0.1% porang glu-comannan), P3 (basal feed + 0.15% porang glucomannan), KJ (basal feed + 0.1% commercial konjac glucomannan), and KM (commercial feed). The results showed that caecal bacterial composition of porang glucomannan treatment had similarity with konjac glucomannan and basal feed. Diversity index and species number of porang glucomannan treatment was higher than konjac glucomannan. Gluco-mannan prebiotics had higher Lactobacillus while the lowest Clostridium was obtained in 0.1% porang glucomannan treatment. The inclusion of glucomannan prebiotics gave no negative effect on the per-formance of broilers.